2016
DOI: 10.21037/jtd.2016.03.64
|View full text |Cite
|
Sign up to set email alerts
|

Limiting the risk of cardiac toxicity with esophageal-sparing intensity modulated radiotherapy for locally advanced lung cancers

Abstract: Background: Intensity modulated radiotherapy (IMRT) is routinely utilized in the treatment of locally advanced non-small cell lung cancer (NSCLC). RTOG 0617 found that overall survival was impacted by increased low (5 Gy) and intermediate (30 Gy) cardiac doses. We evaluated the impact of esophageal-sparing IMRT on cardiac doses with and without the heart considered in the planning process and predicted toxicity compared to 3D-conventional radiotherapy (3DCRT). Methods: Ten consecutive patients with N2 Stage II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The secondary analyses of RTOG 0617 suggest that lower heart doses correlate with improved OS and QoL, and that IMRT can better spare the heart than 3DCRT, consistent with the majority of planning studies (21)(22)(23)(24)26,29,63). In a pooled analysis of dose escalation trials using 3DCRT to treat stage III NSCLC in the setting of induction/concurrent chemotherapy, Wang et al found that 23% of patients experienced a symptomatic cardiac event at a median of 26 months to first event posttreatment, and that higher heart doses and baseline cardiac morbidity predicted for these events (67).…”
Section: Rtog 0617 and Secondary Analysessupporting
confidence: 66%
See 1 more Smart Citation
“…The secondary analyses of RTOG 0617 suggest that lower heart doses correlate with improved OS and QoL, and that IMRT can better spare the heart than 3DCRT, consistent with the majority of planning studies (21)(22)(23)(24)26,29,63). In a pooled analysis of dose escalation trials using 3DCRT to treat stage III NSCLC in the setting of induction/concurrent chemotherapy, Wang et al found that 23% of patients experienced a symptomatic cardiac event at a median of 26 months to first event posttreatment, and that higher heart doses and baseline cardiac morbidity predicted for these events (67).…”
Section: Rtog 0617 and Secondary Analysessupporting
confidence: 66%
“…Planning studies comparing IMRT to 3DCRT for NSCLC have consistently demonstrated that IMRT allows for superior coverage of the PTV and greater avoidance of healthy lung parenchyma, heart, esophagus and spinal cord (21)(22)(23)(24)(25)(26)(27)(28)(29). When designing IMRT plans, beam angle optimization determines which OARs will be preferentially spared.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis by Woodford et al compared normal tissue doses among 3 plans for 10 patients with N2 NSCLC: (1) 3D-CRT, (2) IMRT, and (3) IMRT with cardiac constraints 20 . With a prescription dose of 60 Gy and normalization for target coverage, IMRT significantly reduced the dose to the esophagus and heart compared with 3D-CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although comparisons of 3D-CRT and IMRT for lung cancer have been reported in the literature, few have directly quantified the dosimetric benefit of IMRT. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 The limitations and shortcomings of these studies likely influence current reimbursement policies and practice patterns in which 3D-CRT is the default approach; thus, quantifying the potential advantage with this technology is important. Using a unique, prospectively obtained dataset, we sought to assess this question.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced heart disease (RIHD) often results from radiotherapy for thoracic malignant tumors such as breast, esophageal, and central lung cancer (1)(2)(3)(4). RIHD may include acute pericarditis, coronary atherosclerosis, myocardial injury, cardiac conduction system abnormality, and heart valve disease (5) and the few studies investigating the pathogenesis of RIHD show cardiac conduction abnormality, arrhythmia, and intracardiac conduction block as its main manifestations (6).…”
Section: Introductionmentioning
confidence: 99%